Предмет: Математика,
автор: nastya2004101
Упростите выражение – 4(2,3x – 3) – (5 – 2,6x) + 3(0,6x – 2) и вычислите его значение при х= 5/12
Ответы
Автор ответа:
0
-9,2х+12-5+2,6х+1,8х-6=-4,8х+1
-48/10*5/12+1=-2+1=-1
-48/10*5/12+1=-2+1=-1
Автор ответа:
0
4(2,3x – 3) – (5 – 2,6x) + 3(0,6x – 2)= 9,2x - 12 - 5 + 2,6x + 1,8x - 6 = 13,6x - 22, если x = ,
то 13,6 * = - 22 = -16,3
то 13,6 * = - 22 = -16,3
Похожие вопросы
Предмет: История,
автор: loveliteshoot
Предмет: Информатика,
автор: oksanaryzhuk0589
Предмет: Английский язык,
автор: nikita919289
Предмет: Литература,
автор: 19016
Предмет: Информатика,
автор: tokmakovpasha